Design of Chained-Function Dual-band Waveguide Filter Based on Dual-mode Resonators - Ng, C.L. (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper introduces an approach to design a dual-mode dual-band waveguide filter that operates within sub-6 GHz frequency. This approach can further reduce the size of the dual-band filter while maintaining the low power loss. The design technique combines chained-response multiband function, chained-function, and dual-mode waveguide filter. For demonstration, a dual-mode dual-band filter which operates in 3.5 GHz is designed and simulated. The filter has a bandwidth of 80 MHz for both passbands and two center frequencies of lower and upper passbands which are located at 3.36 GHz and 3.61 GHz respectively. The theoretical and simulation results are compared and discussed at the end of the paper. Â© 2021 IEEE.